REAL-T: Time Modularization in Reactive Distributed Applications - Pimienta, Camilo; Sanabria, Mateo; Díaz, Daniel; Garzón, Wilmer; Melo, Willson; Arboleda, Hugo; Benavides Navarro, Luis Daniel (Springer Nature, 2018)
In this paper, we propose REAL-T, a distributed event-based language with explicit support for time manipulation. The language introduces automata for operational time manipulation, causality constructs and Linear Temporal Logic for declarative time predicates, and a distributed-time aware event model. We have developed a compiler for the language and a dynamic run-time framework. To validate the proposal we study detection of complex patterns of security vulnerabilities in IoT scenarios.

En este artículo, proponemos REAL-T, un lenguaje distribuido basado en eventos con soporte explícito para la manipulación del tiempo. El lenguaje introduce autómatas para la manipulación del tiempo operacional, construcciones de causalidad y lógica temporal lineal para predicados de tiempo declarativos, y un modelo de eventos de tiempo distribuido. Hemos desarrollado un compilador para el lenguaje y un marco de tiempo de ejecución dinámico. Para validar la propuesta estudiamos la detección de patrones complejos de vulnerabilidades de seguridad en escenarios de IoT.
Keywords: Lenguaje de programación; Programación distribuida; Programación orientada a eventos; Distributed programming; Event oriented programming; Explicit and implicit time management